Detection of monobutyl phthalate in urine and environmental water by a rapid and sensitive fluorescence polarization immunoassay - Liliya I. Mukhametova; Madina R. Karimova; Dmitrii A. Arutiunian; Iliya A. Shanin; Egor E. Ponomarenko; Sergei A. Eremin (One Health Advances)
Abstract Phthalate acid diesters (PAEs) are used as plasticizers in various applications and have accumulated in the environment, where they pose a risk to human health. In the body, PAEs are metabolized to toxic monophthalates. Currently, there are few immunoassays available for the determination of monophthalates. In this study, a fluorescence polarization immunoassay (FPIA) for determining monobutyl phthalate (MBP) was developed. This assay was validated by recovery tests of MBP in artificial urine buffer and wastewater samples. A conjugate of MBP with an amino derivative of fluorescein was synthesized and confirmed to bind to polyclonal antibodies. Two protocols for determining the MBP were developed, using different sample volumes depending on the complexity of the matrix. For urine, the FPIA method had a limit of detection of 100 ng/mL and a detection range of 200–500,000 ng/mL. For water, the limit of detection was 5 ng/mL and the detection range was 30–50,000 ng/mL. The analysis time was 5 min. The developed FPIA is suitable for determination of MBP in river water samples. Because the matrix did not affect the results for water samples, no pretreatment was required. Therefore, water samples can be tested on-site using a small portable FPIA analyzer. This method could be used to determine monophthalates in environmental waters or human biological fluids.